Assembly and annotation of the genome of the sea urchin Tripneustes gratilla - Van der Westhuizen, Hester Christina (Stellenbosch : Stellenbosch University, 2025)
Van der Westhuizen, Hester Christina. 2024. Assembly and annotation of the genome of the sea urchin Tripneustes gratilla. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131950